Case Report: Optical genome mapping enables identification of complex balanced chromosomal rearrangements - Hu, Xiaohang; Guo, Jing; Sang, Haiyang; Yan, Jinyan; Chang, Hong; Liu, Ting; Dong, Haixin; Kong, Min; Tian, Yanjun; Jiang, Liqing (Frontiers in Genetics, 2025)
IntroductionIndividuals with balanced chromosomal rearrangements are at an increased risk for infertility, recurrent miscarriages, and the birth of infants with congenital malformations. Traditional cytogenetic techniques are limited by their low resolution, whereas optical genome mapping offers enhanced capabilities for detecting chromosomal rearrangements and determining genomic localization and orientation. This study sought to evaluate the efficacy of optical genome mapping in identifying complex balanced chromosomal rearrangements that may contribute to fertility challenges.Case presentationA 21-year-old Asian female patient with a history of recurrent abortions was included in the study. Peripheral blood samples were collected for high-resolution karyotyping, chromosomal microarray analysis, and optical genome mapping. The high-resolution karyotype analysis identified complex chromosomal abnormalities. Optical genome mapping has revealed additional cryptic chromosomal aberrations, such as ins (2; 12) (p16.1; q12q12), inv (6) (q21q21), and inv (12) (q12q12), offering a novel perspective on this case. Notably, the disrupted genes, including CRIM1, MUC19, and PRDM1, have not been classified as pathogenic by existing databases.ConclusionThis study underscores the capability of optical genome mapping to deliver comprehensive and precise information. It is anticipated that optical genome mapping will emerge as a valuable cytogenetic tool within clinical genetic methodologies, providing new references and insights for clinical practice in the future.